The involvement of 5-lipoxygenase activating protein in anxiety-like behavior - Joshi, Yash B. (2013)
The 5-lipoxygenase is an enzyme widely expressed in the central nervous system, where its activity is dependent on the presence the 5-lipoxygenase activating protein (FLAP) for the formation of leukotrienes, potent bioactive lipid mediators. Emerging evidence has shown that the FLAP/leukotriene pathway may play a role in neuropsychiatric disease contexts. In this study we investigated whether genetic deficiency of FLAP (FLAPKO) modulated some behavioral aspects in mice, and if this effect was age-dependent. While we observed that FLAPKO mice at 3 and 6 months of age did not different from wild type animals in the elevated plus maze, at 12 months of age they manifested a significant increase in the anxiety-like behavior. By contrast, we observed no differences between FLAPKO mice and their controls at any of the three ages considered when they were tested for working memory in the Y maze paradigm. Additionally, while we found that cFOS protein and message levels were reduced in the brains of animals lacking FLAP, no changes for other transcription factors were detected. Taken together our findings suggest a novel role for FLAP in the pathogenesis of anxiety-like behavior. Future studies of FLAP neurobiology may be attractive for development of anxiolytic therapeutics.